Plant community composition in relation to soil physico-chemical properties of the Ratargul swamp forest, Bangladesh (Dhaka University Journal of Biological Sciences, 2016)
Vegetation composition in relation to soil physical and chemical properties of the Ratargul Swamp Forest was examined in the present study. Vegetation data were collected from 10 different sites by placing quadrats (10 m × 10 m) randomly at a distance of 500 m from each other in the forest area. Soil samples were collected from the centre of the quadrat. Plant species richness and the Shannon Diversity Index (H?) ranged from 3 to 7 and from 0.150 to 1.184 respectively, per quadrat. Among the tree species, Pongamia pinnata (L.) Merr. showed the highest important value index (IVI) value (15.62) indicating the dominance of the species in the forest. Among the shrubs, Schumannianthus dichotomus (Roxb.) Gagnep. showed the highest IVI value (36.25) and Phyllanthus disticha showed the lowest (2.2). Of the herbs, Diplazium esculentum (Retz.) Sw. showed the highest (92.44) and Asparagus racemosus L. showed the lowest (2.2) IVI values. Diameter at breast height (DBH) of P. pinnata (L.) Merr. varied largely from 29.26 to 169.77 cm indicating its growth variability from site to site in the forest. Soil pH, electric conductivity, organic carbon, total nitrogen and total phosphorus also showed a large range of variation in the study area. Redundancy Discriminant Analysis showed that soil moisture, conductivity, organic carbon and total nitrogen were significantly correlated with plant species data. Crataeva nurvala Buch-Ham and Mucuna zygantea DC. correlated with soil organic carbon and moisture content. On the other hand, S. dichotomus (Roxb.) Gagnep. showed significant correlation with soil conductivity. Results, thus, indicate that vegetation composition is related with soil properties in the Ratargul Swamp Forest.Dhaka Univ. J. Biol. Sci. 25(1): 1-8, 2016